Publication performance of economists and economics departments in Turkey (1999-2003) - ÇOKGEZEN, MURAT (My University, 2006)
This is the first study evaluating the publication performances of economists and economics departments in Turkey. The international (article) publication performance of Turkish economic departments in general is found to be rather poor. There is a wide gap in particular between the top five universities and the economists affiliated to them and those outside the top five. The paper also provides evidence in favour of private higher education. The publication patterns of economists in Turkey are shown to be similar to those of their counterparts in the rest of the world. © Blackwell Publishers Ltd and the Board of Trustees of the Bulletin of Economic Research, 2006.
Keywords: Economics departments; Economists; Rankings; Turkey